Evaluating The Effectiveness Of A Conceptual Skill Training : A Quasi-Experimental - Lee, Kar Ling (2007)
Training and development are viewed as expensive investments for a business organization and is often neglected during recession. One of the frequently cited reasons for not focusing on training and development was because the value and contribution could not be effectively ascertained. Although training evaluation tools and instruments abound, existing methodologies do not provide adequate answers for all types of training, more so for management development programs Even though problem solving and decision-making skill